Adolescents' Perceived Barriers to Physical Activity during the COVID-19 Pandemic - Carlos Mata; Marcos Onofre; João Martins (MDPI AG, 2022)
During the COVID-19 pandemic, adolescents' routines were deeply affected, which negatively impacted their level of PA. Knowing the barriers to PA in adolescence is relevant, because the perception of more barriers is one of the most consistent negative correlates of PA participation. The purpose of this study was to analyze and compare the barriers perceived by adolescents during the COVID-19 pandemic by sex, education level, PA level, and BMI. A total of 1369 students (621 boys and 748 girls; mean age: 14.4 years; SD: 1.74) participated in the study. The chi-square test was used to analyze the differences between groups. Only 3.1% of the adolescents complied with the international guidelines for PA. In general, the barriers with the highest prevalence were the COVID-19 pandemic, lack of time, and taking time away from study. The number of perceived barriers to PA was higher among girls, younger, and inactive participants. Boys selected more the barriers due to COVID-19 than girls, and students with normal weight chose more barriers than those with overweight. This study provides information on adolescents' PA barriers during the COVID-19 pandemic and draws attention to the negative effects that restrictive measures have had on adolescents' PA levels.